Natural Syntax: The English indefinite article - Orešnik, Janez (Adam Mickiewicz University, 2010)
The framework of this paper is Natural Syntax initiated by the author in the tradition of (morphological) naturalness as established by Wolfgang U. Dressler and †Willi Mayerthaler. Natural Syntax is a developing deductive theory. The naturalness judgements are couched in naturalness scales, which follow from the basic parameters (or “axioms”) listed at the beginning of the paper. The predictions of the theory are calculated in what are known as deductions, the chief components of each being a pair of naturalness scales and the rules governing the alignment of corresponding naturalness values. Natural Syntax is here exemplified with selected language data bearing on the use of the English indefinite article. Some recent work related to Natural Syntax: Orešnik 2007a–e; 2008a–c; 2009a,b; 2009 (with Varja Cvetko-Orešnik). (Only work published in English is mentioned).
Keywords: naturalness; indefiniteness; indefinite article; syntax